LA CITTÀ PALINSESTO/I Tracce, sguardi e narrazioni sulla complessità dei contesti urbani storici: Memorie, storie, immagini - Capano, Francesca (Storia e iconografia dell'architettura, delle città e dei siti europei, 2020)
The subject of this bookis the complex heritage of traces, images and narratives that build the contemporary city. We are talking about urban realities that must be reread and recounted in parts, by layers, backwards, in such a way asto be able to unravel that intricate skein of overlaps that have occurred over time. They are traces very often still in situ, sometimes hidden, sometimes modified, but also distracted, fragmented, poorly concealed and hidden.